Effects of combining hyaluronic acid hydrogel with injectable platelet rich fibrin on apical papilla stem cells proliferation and differentiation - Azal H. Al-Masoody; Nasrin Asadi; Hadiseh Mohammadpour; Mahshid Hodjat; Tahereh Sadat Jafarzadeh Kashi (BMC Oral Health)
Abstract Background This study examines the effects of combining hyaluronic acid hydrogel (HA) and injectable platelet-rich fibrin (iPRF) on the proliferation, migration and odontogenic differentiation of apical papilla stem cells (SCAP). The goal is to enhance regenerative endodontic procedures (REPs) with more effective regenerative biomaterials. Method SCAPs were cultured on HA, both with and without iPRF in a 3D culture system. Also, the effect of iPRF in a 2D culture was assessed. Cell proliferation was evaluated using MTT assay, for analysing cell migration the Transwell Migration assay was utilized. To assess the odontogenic differentiation, the alkaline phosphatase assay was performed, and the gene expression of odontogenic markers including Collagen type I (Col-1), Dentin matrix protein1 (DMP-1), and Dentin sialophosphoprotein (DSPP) were examined by real-time Polymerase chain reaction (PCR). Results iPRF induced cell proliferation in 2D and HA 3D cultures compared to the control groups. The HA/iPRF mixture showed synergistic effects in odontogenic gene expression and migration assays. However, the iPRF group showed the most alkaline phosphatase expression after 7 days. Cells in a 3D culture system combining HA and iPRF demonstrated enhanced odontogenic differentiation and chemotaxis compared to either component used separately. Conclusion The combination of HA and iPRF shows promise for future regenerative endodontic applications.